2005
DOI: 10.1007/s00383-005-1567-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of anorectal malformations in Varanasi, India: a long-term review of single and three stage procedures

Abstract: To compare the results of the staged procedure (Group A) with the primary single stage posterior sagittal anorectoplasty (PSARP) procedure (Group B) for high and intermediate anorectal anomalies. Four hundred ninety cases of primary single stage procedure done over a period of seven years (1996-2003) were compared with 458 out of 763 cases of staged procedure (Historical control) that underwent all three stages done from 1989 to 1996. Two hundred cases that had been in regular follow up in Group A and 254 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 11 publications
(11 reference statements)
1
22
0
Order By: Relevance
“…(8,9) Various surgeons have reported that there is no significant difference in multistage and single stage procedure. (10)(11)(12)(13)(14)(15)(16)(17) Our series is small for statistical analysis, but the results are in accordance with these reported series outcome in terms of continence can be achieved by careful anterior sagittal surgical dissection. Anovestibular fistula can be repaired in one stage with meticulous pre-and postoperative bowel management.…”
Section: Discussionsupporting
confidence: 79%
“…(8,9) Various surgeons have reported that there is no significant difference in multistage and single stage procedure. (10)(11)(12)(13)(14)(15)(16)(17) Our series is small for statistical analysis, but the results are in accordance with these reported series outcome in terms of continence can be achieved by careful anterior sagittal surgical dissection. Anovestibular fistula can be repaired in one stage with meticulous pre-and postoperative bowel management.…”
Section: Discussionsupporting
confidence: 79%
“…All patients underwent single stage anterior sagittal anorectovaginoplasty (ASARVP) without diverting colostomy. Most of the patients (about 95%) suffering with anorectal malformation either low or high were treated with single stage surgery at our center [15,16] as reported earlier the continence result of single stage repair in neonatal age group is safe, good results and minimal complications. The results were good in present study and we observed only one major complication.…”
Section: Discussionmentioning
confidence: 94%
“…Aluwihare [16] favored primary perineal rectovaginoplasty for supralevator imperforate anus in female neonates and concluded that operation is easier than other available procedures, with minimal complications. Single stage repair for anorectal malformations had been advocated by few studies [15][16][17][18] with good results and concluded that single stage repair in neonate is safe with minimal complications.…”
Section: Discussionmentioning
confidence: 99%
“…We have been doing one stage treatment for many years, despite all the risks and now our 10 years data demonstrates a comparable outcome with 5% mortality and 70% socially acceptable continence rates. 2,3,4 The babies with bowel atresia have had a steadily improving outcome with the passing years. The distinctly poor outcome has been seen in a rare variant of small bowel atresia called apple peel deformity where the mesentry of the atretic bowel is abnormal.…”
Section: Discussionmentioning
confidence: 98%